Analisis Kebutuhan Layanan Bimbingan dan Konseling Kelompok Berbasis TPACK - Uruk, Febriady Huta; Permana, Satya Anggi (Dharmas Education Journal (DE_Journal), 2025)
This study aims to describe and analyze students' needs for Group Guidance and Counseling learning materials based on TPACK (Technological Pedagogical Content Knowledge) at STKIP Muhammadiyah Sungai Penuh. The research used a descriptive quantitative approach. Data was collected through a questionnaire designed based on the Need, Lack, Want (NLW) framework integrated with the TPACK domains. The questionnaire was distributed to 30 fourth-semester students from the Guidance and Counseling Study Program, selected using a purposive sampling technique. The data were analyzed using descriptive statistics. The results revealed: (1) Need: 82% of students highly require the presence of a TPACK-based e-book that holistically integrates content, pedagogy, and technology; (2) Lack: 76% of students faced difficulties in understanding the material through conventional textbooks, which were deemed no longer relevant; (3) Want: 85% of students desire interactive features such as group dynamics simulations, interactive quizzes, and role-play guides in the e-book.